QUALITY MATTER FOR (INDONESIA) PRIVATE HIGHER EDUCATION INSTITUTION - Gembong Baskoro (Institute of Research and Community Outreach - Petra Christian University, 2009)
Quality in higher education is nowadays becoming important aspect for universities in order for them to participate in improving Indonesia competitiveness by mean of improving human development index. However, quality itself is not a simple term to be understood. Therefore the main objective of this paper is to elaborate quality matter especially for Private Higher Education Institution. It is expected that this paper can provide another insight for private Higher Education Institution to improve the quality. This paper tries to approach the quality by understanding its philosophy as well as its practical approach in Industry. Of course, there are always rooms for improvement.